A novel non-canonical rectifying calcium channel in rice triggers cell death mediated robust immunity - Wu, Jun; Liu, Jianbin; Xiao, Gui; Liu, Hai; Liang, Yi; Yi, Zhaofeng; Bin, Bai; Liang, Xiushuo; Luo, Sheng; Yang, Jie; Xue, Shaowu; Sun, Wenxian; et al. (Springer, 2025)
Plants utilize calcium as a signaling molecule to regulate innate immunity, including PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI), in addition to controlling growth and development1,2. Recent extensive research has highlighted that the activation of calcium ion (Ca2+) channels during PTI and the formation of Ca2+ channels during ETI are crucial for plant immunity3. However, comprehension on how crops substantially augment immunity through the enhancement of Ca2+ channel activity remains limited. Here, we report a rice lesion mimic mutant, called etd1 (elicitors triggered cell death 1), which also triggers cell death formation upon the challenge of rice blast elicitors. The recessive gain-of-function gene etd1 encodes a hypermorphic haplotype of OsCNGC13 which contains a single amino acid substitution of glycine-to-glutamate at the position of 483rd amino acid. The etd1 forms a novel non-canonical rectifying Ca2+ channel that significantly enhances Ca2+ influx. We position that etd1-driven excessive Ca2+ influx disrupts cellular calcium homeostasis, thereby triggering pathogen-induced cell death and conferring robust and broad-spectrum immunity to the rice blast pathogen.